Effectiveness of Interactive Tools in Online Health Care Communities: Social Exchange Theory Perspective - Ren, Dixuan; Ma, Baolong (JMIR Publications, 2021)
BackgroundAlthough the COVID-19 pandemic will have a negative effect on China's economy in the short term, it also represents a major opportunity for internet-based medical treatment in the medium and long term. Compared with normal times, internet-based medical platforms including the Haodf website were visited by 1.11 billion people, the number of new registered users of all platforms increased by 10, and the number of new users' daily consultations increased by 9 during the pandemic. The continuous participation of physicians is a major factor in the success of the platform, and economic return is an important reason for physicians to provide internet-based services. However, no study has provided the effectiveness of interactive tools in online health care communities to influence physicians' returns. ObjectiveThe effect of internet-based effort on the benefits and effectiveness of interactive effort tools in internet-based health care areas remains unclear. Thus, the goals of this study are to examine the effect of doctors' internet-based service quality on their economic returns during COVID-19 social restrictions, to examine the effect of mutual help groups on doctors' economic returns during COVID-19 social restrictions, and to explore the moderating effect of disease privacy on doctors' efforts and economic returns during COVID-19 social restrictions. MethodsOn the basis of the social exchange theory, this study establishes an internet-based effort exchange model for doctors. We used a crawler to download information automatically from Haodf website. From March 5 to 7, 2020, which occurred during the COVID-19 pandemic in China, cross-sectional information of 2530 doctors were collected. ResultsHierarchical linear regression showed that disease privacy (β=.481; P<.001), reputation (β=.584; P<.001), and service quality (β=.560; P<.001) had a significant positive effect on the economic returns of the physicians. The influence of mutual help groups on earnings increases with an increase in the degree of disease privacy (β=.189; P<.001), indicating that mutual help groups have a stronger effect on earnings when patients ask questions about diseases regarding which they desire privacy. ConclusionsFor platform operators, the results of this study can help the platform understand how to improve doctors' economic returns, especially regarding helping a specific doctor group improve its income to retain good doctors. For physicians on the platform, this study will help doctors spend their limited energy and time on tools that can improve internet-based consultation incomes. Patients who receive internet-based health care services extract information about a doctor based on the doctor's internet-based efforts to understand the doctor's level of professionalism and personality to choose the doctor they like the most. The data used in this study may be biased or not representative of all medical platforms, as they were collected from a single website.